Application of MR-derived cross-sectional guideline of cervical spine muscles to validate neck surface electromyography placement. (December 2018) - Alizadeh, Mina; Knapik, Gregory G.; Marras, William S.
Abstract: The importance of surface-EMG placement for development and interpretation of EMG-assisted biomechanical models is well established. Since MR has become a reliable noninvasive cervical spine musculoskeletal diagnostic tool, this investigation attempted to illustrate the anatomical relationships of individual cervical spine muscles with their paired surface-EMG electrodes. The secondary purpose of this investigation was to provide an MR cross-sectional pictorial and descriptive guideline of the cervical spine musculature. MR scans were performed on a healthy adult male subject from skull to manubrium of the sternum. Prior to scanning, MR safe markers were placed over neck muscles following surface EMG placement recommendations. Twenty-three neck muscles were traced manually in each of 267 scan slices. 3-D models of the neck musculoskeletal structure were constructed to aid with understanding the complex anatomy of the region as well as to identify correct EMG electrode locations and to identify muscles' curved lines-of-action. 3D models of the MR-safe markers were constructed relative to the target muscles. Based on the findings of this study, muscle palpation and bony landmarks can be used to effectively identify appropriate surface EMG electrode locations to record upper trapezius, middle trapezius, semispinalis capitis, splenius capitis, levator scapulae, scalenus, sternocleidomastoid and hyoid muscles activities.